Hippocampal adaptation to high altitude: a neuroanatomic profile of hippocampal subfields in Tibetans and acclimatized Han Chinese residents - Zhang, Lianqing; Meng, Jinli; Li, Hailong; Tang, Mengyue; Zhou, Zan; Zhou, Xingning; Feng, Li; Li, Xiangwei; Guo, Yongyue; He, Yuanyuan; He, Wanlin; Huang, Xiaoqi (Frontiers in Neuroanatomy, 2022)
The hippocampus is highly plastic and vulnerable to hypoxia. However, it is unknown whether and how it adapts to chronic hypobaric hypoxia in humans. With a unique sample of Tibetans and acclimatized Han Chinese individuals residing on the Tibetan plateau, we aimed to build a neuroanatomic profile of the altitude-adapted hippocampus by measuring the volumetric differences in the whole hippocampus and its subfields. High-resolution T1-weighted magnetic resonance imaging was performed in healthy Tibetans (TH, n = 72) and healthy Han Chinese individuals living at an altitude of more than 3,500 m (HH, n = 27). In addition, healthy Han Chinese individuals living on a plain (HP, n = 72) were recruited as a sea-level reference group. Whereas the total hippocampal volume did not show a significant difference across groups when corrected for age, sex, and total intracranial volume, subfield-level differences within the hippocampus were found. Post hoc analyses revealed that Tibetans had larger core hippocampal subfields (bilateral CA3, right CA4, right dentate gyrus); a larger right hippocampus–amygdala transition area; and smaller bilateral presubiculum, right subiculum, and bilateral fimbria, than Han Chinese subjects (HH and/or HP). The hippocampus and all its subfields were found to be slightly and non-significantly smaller in HH subjects than in HP subjects. As a primary explorational study, our data suggested that while the overall hippocampal volume did not change, the core hippocampus of Tibetans may have an effect of adaptation to chronic hypobaric hypoxia. However, this adaptation may have required generations rather than mere decades to accumulate in the population.